Well Test Analysis Using Pressure Derivative Method at Gas Well X-1 - Muhammad Handis Maulana; Muhammad Taufiq Fathaddin; Hari Karyadi Oetomo (Journal of Earth Energy Science, Engineering, and Technology, 2018)
Wells X-1 is a gas condensate well which located in lapangan X, Sulawesi Island. At well X-1 well test was conducted using pressure build up, where the analysis was conducted with objective to determine the reservoir characteristic of X-1 wells such as permeability, skin, flow efficiency and investigation radius. In the pressure build up test, the horner plot and derivation analysis using pseudo pressure and P2 approaches were applied with the gas well X-1 has a reservoir pressure of 2555 psia. The analysis is done using saphir 3.20 and Ms.Excel software where the results of the counsel to see if there is any possibility of formation damage. X-1 is also known as homogeneous with a fault boundary present in the fault located at a certain distance from the well X-1 in which the fault is only one direction from the reservoir. The pressure derivative plot analysis was conducted with two methods such as two-point method and three-point method, where the result of the overlay of the derivative curve corresponds to the deviation of the calculation result method which is less than 10%. The horner plot analysis is also done with the ψ(P) pseudo pressure and P2 approach which is the result of horner plot analysis using pseudo pressure ψ(P) pseudo pressure in saphir 3.20 obtained the slope (m), permeability, and skin values respectively were 3.22432E + 5 psi2/cp, 132 mD, and 21.6, whereas Ms.Excel results obtained the price of slope (m), permeability, and skin respectively were 320890.61 psi2/cp, 134.83 mD, and 21.1. To analyze the horner plot using the P2 approach at saphir 3.20 the value of slope (m), permeability, and skins values respectively were 5495.07 psi2/cp, 125 mD, and 21.3 and for the results of Ms. Excel the price of slope (m), permeability, and skin respectively were 5451.66 psi2/cp, 147,29 mD, and 20,1. Positive skin results in both methods of horner plot and derivative plot indicate the well is damaged and need to be stimulated.